Conventional Border Molding versus Digital Impression on Complete Denture Impression: A Review - Nusima Mohamed; Hazira M. Yusof; Nor Faharina Abdul Hamid; Norlela Yacob (Bentham Science, 2024)
Indexed by WOS/Scopus/ERA